Age-Related Decrease in Stress Responsiveness and Proactive Coping in Male Mice - Oh, Hee-Jin; Song, Minah; Kim, Young Ki; Bae, Jae Ryong; Cha, Seung-Yun; Bae, Ji Young; Kim, Yeongmin; You, Minsu; Lee, Younpyo; Shim, Jieun; Maeng, Sungho (Frontiers in Aging Neuroscience, 2018)
Coping is a strategic approach to dealing with stressful situations. Those who use proactive coping strategies tend to accept changes and act before changes are expected. In contrast, those who use reactive coping are less flexible and more likely to act in response to changes. However, little research has assessed how coping style changes with age. This study investigated age-related changes in coping strategies and stress responsiveness and the influence of age on the processing of conditioned fear memory in 2-, 12-, and 23-month-old male mice. Coping strategy was measured by comparing the escape latency in an active avoidance test and by comparing responses to a shock prod. The results showed that proactivity in coping response gradually decreased with age. Stress responsiveness, measured by stress-induced concentration of corticosterone, was also highest in 2-month-old mice and decreased with age. Consolidation of fear memory was highest in 12-month-old mice and was negatively correlated with the degree of stress responsiveness and proactivity in coping. Fear extinction did not differ among age groups and was not correlated with stress responsiveness or the proactivity of coping. However, the maintenance of extinct fear memory, which was best in 2-month-old mice and worst in 12-month-old mice, was negatively correlated with stress responsiveness but not with coping style. Age-dependent changes in the expression of glucocorticoid receptor(GR) and its regulatory co-chaperones, which are accepted mechanisms for stress hormone stimulation, were measured in the hippocampus. The expression of GR was increased at 12 months compared to other age groups. There were no differences in Hsp70 and BAG1 expression by age. These results can be summarized as follows: 1) stress responsiveness and proactivity in coping decreased with age class; 2) consolidation of fear memory was negatively correlated with both stress responsiveness and proactivity; however, maintenance of extinct fear memory was negatively correlated with stress responsiveness only; and 3) consolidation and maintenance of extinct fear memory appeared to be more influenced by factors other than stress reactivity and proactivity in coping, such as the amount of hippocampal glucocorticoid expression.